Introduction - Antonio De Lauri (Antropologia, 2013)
This volume explores the anthropological perspectives on war, emphasizing its social, cultural, and political dimensions. It examines the interplay of economic interests, stigmatization, propaganda, and the militarization of humanitarian interventions. The essays advocate for a counter-rhetoric of war, challenging dominant narratives and highlighting war's ethical implications. Through ethnographic sensitivity, the collection provides a transcultural investigation into the continuity between war and peace, encouraging critical reflection on contemporary warfare​​.